2022
DOI: 10.1186/s12887-022-03440-w
|View full text |Cite
|
Sign up to set email alerts
|

Making a HIIT: study protocol for assessing the feasibility and effects of co-designing high-intensity interval training workouts with students and teachers

Abstract: Background High-intensity interval training (HIIT) is an effective strategy for improving a variety of health outcomes within the school setting. However, there is limited research on the implementation of school-based HIIT interventions and the integration of HIIT within the Health and Physical Education (HPE) curriculum. The aims of the Making a HIIT study are to: 1) describe the methodology and evaluate the feasibility of co-designing HIIT workouts with students and teachers in HPE; 2) deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Existing studies have found that some scholars have put forward the conceptual model and mechanism of psychological crisis management based on big data [ 26 , 27 ], but the operability is not strong. Based on this, on the basis of analyzing the concept and characteristics of college students' psychological crisis, combined with the problems and the needs of college students' psychological health education, this paper puts forward suggestions on deepening the application of technology in college students' psychological health education, systematically builds a college students' psychological crisis early warning system under big data, and puts forward scientific, targeted, and effective countermeasures and reference methods for college students' psychological crisis, in order to provide theoretical and methodological support for college mental health management.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have found that some scholars have put forward the conceptual model and mechanism of psychological crisis management based on big data [ 26 , 27 ], but the operability is not strong. Based on this, on the basis of analyzing the concept and characteristics of college students' psychological crisis, combined with the problems and the needs of college students' psychological health education, this paper puts forward suggestions on deepening the application of technology in college students' psychological health education, systematically builds a college students' psychological crisis early warning system under big data, and puts forward scientific, targeted, and effective countermeasures and reference methods for college students' psychological crisis, in order to provide theoretical and methodological support for college mental health management.…”
Section: Introductionmentioning
confidence: 99%
“…The Making a HIIT study has previously been described in detail in Chapter Three [207]. An overview of the study is provided below to contextualise the findings.…”
Section: Methodsmentioning
confidence: 99%
“…The Making a HIIT study is a real-world school-based HIIT intervention adapted for implementation at three separate schools using HIIT workouts co-designed at each school [207]. Teachers led the intervention within Year 7 and 8 health and physical education (HPE) lessons and adapted the intervention to fit the school and class context [207]. The aim of this paper was to comprehensively evaluate the implementation of the Making a HIIT study using the Framework for Effective Implementation [161].…”
Section: High Intensity Interval Training (Hiit) Is Gaining Popularit...mentioning
confidence: 99%
See 2 more Smart Citations